1977
DOI: 10.1002/jsfa.2740281003
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of green aroma of raw mango (Mangifera indica L.)

Abstract: The latex of two varieties of mango, Alphonso and Batali, was collected during the de-stalking of freshly picked matured unripe (raw) fruit. The essential oil of each of the mango latices was isolated by high vacuum distillation at ambient temperature. The major component of each essential oil possessing the characteristic aroma of green mango, was isolated by preparative gas-liquid chromatography and was characterised as cis-ocimene and 8-myrcene, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 4 publications
2
21
0
Order By: Relevance
“…Ocimene, an acyclic monoterpene, is an essential oil that is widely distributed in plants and contributes to the aroma of many fruits. 15,16 Refrigerated storage of the fruit for a period of 24 h caused a decrease in esters relative to the freshly cut fruit. The highest losses occurred in the major compounds, ranging from about 60% of ethyl hexanoate to over 75% of methyl 5-hexenoate.…”
Section: Resultsmentioning
confidence: 99%
“…Ocimene, an acyclic monoterpene, is an essential oil that is widely distributed in plants and contributes to the aroma of many fruits. 15,16 Refrigerated storage of the fruit for a period of 24 h caused a decrease in esters relative to the freshly cut fruit. The highest losses occurred in the major compounds, ranging from about 60% of ethyl hexanoate to over 75% of methyl 5-hexenoate.…”
Section: Resultsmentioning
confidence: 99%
“…Both chemicals were major components in the hydrocarbons. Gholap and Bandyopadhyay (1977) reported that hydrocarbon terpenes such as myrcene and (Z)-␤-ocimene were responsible for the green aroma of the fresh Indian mango, Alphonso and Batali cultivars. However, we detected the hydrocarbons at low concentrations in the oil.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, antioxidant compounds in mango peel fibres were reported to have beneficial effects on health in high-dietary-fibre diets (Larrauri et al, 1997). Gholap and Bandyopadhyay (1977) studied on the volatiles in the latex of green raw mango. Utilization of mango peels for industrial purpose (Rashad et al, 1990) must be encouraged more than before.…”
mentioning
confidence: 99%
“…High vacuum distillation (HVD). High vacuum distillation was carried out according to the procedure reported in literature (Bandyopadhyay, Gholap, & Sreenivasan, 1973;Gholap & Bandyopadhyay, 1977). Cut ash gourd (200 g) was frozen in liquid nitrogen before use.…”
Section: Methodsmentioning
confidence: 99%